2016
DOI: 10.1016/j.neurobiolaging.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Emotional bias of sleep-dependent processing shifts from negative to positive with aging

Abstract: Age-related memory decline has been proposed to result partially from impairments in memory consolidation over sleep. However, such decline may reflect a shift toward selective processing of positive information with age rather than impaired sleep-related mechanisms. In the current study, young and older adults viewed negative and neutral pictures or positive and neutral pictures and underwent a recognition test after sleep or wake. Subjective emotional reactivity and affect were also measured. Compared to wak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 66 publications
(85 reference statements)
6
37
0
Order By: Relevance
“…Further, we 21,22 and others 23,24 demonstrated sleep and wake differentially impact emotion generation (eg, self-reported valence ratings). Specifically, when individuals are shown the same set of negative stimuli twice (with a period of sleep between viewing sessions), emotionality to negative stimuli is preserved.…”
Section: Statement Of Significancementioning
confidence: 63%
See 4 more Smart Citations
“…Further, we 21,22 and others 23,24 demonstrated sleep and wake differentially impact emotion generation (eg, self-reported valence ratings). Specifically, when individuals are shown the same set of negative stimuli twice (with a period of sleep between viewing sessions), emotionality to negative stimuli is preserved.…”
Section: Statement Of Significancementioning
confidence: 63%
“…[20][21][22] In a separate study, we found sleep-dependent memory consolidation may causally impact subsequent (ie, next-day) mood. Specifically, we found sleep staging predicts post-sleep affect/mood but only when sleep-dependent emotional memory consolidation occurred.…”
Section: Statement Of Significancementioning
confidence: 76%
See 3 more Smart Citations